Sistema ERP basado en inteligencia de negocios para el proceso de administración y toma de decisiones de la distribuidora DIMACO de la ciudad de Tulcán - Benavides Villarreal, Diego Andrés (2017)
The ERP system (Enterprise Resource Planning) based on Business Intelligence for the process of management and decision-making of Dimaco - Tulcán, is an application which aims to unify in modular form, most parts of the processes carried out by the Company. This way, the Company will optimize the management and decision-making through the treatment and debugging data. The methodology used was the cycle of life of the software, such as; analysis, design, construction and testing. By using this cycle, tools and steps were obtained to fulfill the requirements that ensure the quality and performance of the application according to the requirements of work, The system belongs to the research line of software development and programming. By applying this research, business intelligence and enterprise resource planning systems are integrated. Also, most departments or business management areas that help monitoring them through a single platform that facilitates the exchange of information are integrated, too.